Word-Wall Education Game to Enhance Literacy Skills in Elementary Schools - Rahmat Rahmat; Ismail Ismail; Nursin Nursin (Universitas Muhammadiyah Enrekang, 2024)
Literacy is a crucial basic skill in education, helping students understand texts, express thoughts in writing, and gain broader knowledge. This research uses a quantitative method with a pretest-posttest control group design research design on grade 5 students of SD Negeri 132 Malele-Enrekang consisting of a control group (traditional method) and an experimental group (Word Wall Game). The research results show that the Word Wall Game significantly improves students' literacy skills. There was a consistent increase in reading, writing, and literacy understanding in the group that used the Word Wall Game compared to the control group. Teacher response to the Word Wall Game has been generally positive, seeing it as a tool that increases student engagement and creates a fun learning environment. This research concludes that the Word Wall Game has great potential in increasing the literacy of elementary school students. The practical implication is that the Word Wall Game can be used by teachers as an innovative learning tool to increase student literacy at the elementary level, creating more interesting and effective learning.